Effects of exercise training on nigrostriatal neuroprotection in Parkinson’s disease: a systematic review - Shahid Ishaq; Iqbal Ali Shah; Shin-Da Lee; Shin-Da Lee; Bor-Tsang Wu (Frontiers in Neuroscience)
IntroductionParkinson’s disease (PD) is characterized by progressive neurodegeneration within the nigrostriatum, leading to motor dysfunction. This systematic review aimed to summarize the effects of various exercise training regimens on protein or gene expression within the nigrostriatum and their role in neuroprotection and motor function improvement in animal models of Parkinson’s disease (PD).MethodsPubMed, EMBASE, and Web of Science were searched up to June 2024 and included sixteen studies that adhere to PRISMA guidelines and CAMARADES checklist scores ranging from 4 to 6 out of 10. Various exercise training regimens, administered 5 days per week for 6.5 weeks, were applied to MPTP, 6-OHDA, and PFF-α-synuclein-induced PD animal models.ResultsExercise training was found to downregulate the inflammatory pathway by attenuating α-synuclein aggregation, inhibiting the TLR/MyD88/IκBα signaling cascade and NF-κB phosphorylation, and decreasing pro-inflammatory cytokines IL-1β and TNF-α while increasing anti-inflammatory cytokines IL-10 and TGF-β within the nigrostriatum. It also inhibited the ASC and NLRP3 inflammasome complex and reduced the BAX/ Bcl-2 ratio and caspase-1/3 proteins, thereby decreasing neuronal apoptosis in the nigrostriatum. Exercise training elevated the expression of Pro-BDNF, BDNF, GDNF, TrkB, and Erk1/2, providing neurotrophic support to dopaminergic neurons. Furthermore, it upregulated the dopaminergic signaling pathway by increasing the expression of TH, DAT, PSD-95, and synaptophysin in the nigrostriatum.DiscussionThe findings suggested that exercise training downregulated inflammatory and apoptotic pathways while upregulated BDNF/GDNF pathways and dopaminergic signaling within the nigrostriatum. These molecular changes contributed to neuroprotection, reduced dopaminergic neuron loss, and improved motor function in PD animal models.Systematic review registrationCRD42024484537 https://www.crd.york.ac.uk/prospero/#recordDetails.